The rise in house prices in China: Bubbles or fundamentals? - HU, Jianying (Institutional Knowledge at Singapore Management University, 2006)
The dramatic rise of house prices in many cities of China has brought huge attention from both the governmental and academic circles. There is a huge debate on whether the increasing house prices are driven by market fundamentals or just by speculation. Like Levin and Wright (1997a, 1997b), we decompose house prices in China into fundamental and non−fundamental components. We also consider potential nonlinear feedback from the historical growth rate of house prices on the current house prices and propose a semiparametric approach to estimate the speculative components in the model. We demonstrate that the non−fundamental part contributes a relatively small proportion of the rise of house prices in China.